The State of Diversity in Academic Plastic Surgery Faculty across North America. Issue 11 (16th November 2021) - Chawla, Sahil; Chawla, Amey; Hussain, Mehwish; Karimuddin, Ahmer A.; Khosa, Faisal
Abstract : Background: Gender and racial disparity is prevalent in all surgical subspecialties with women and racial groups historically underrepresented in academic plastic surgery. This study evaluated gender and racial profiles of academic plastic surgery faculty in North America and correlated both with research productivity and its effect on academic ranks of faculty in plastic surgery. Methods: In this cross-sectional study, we compiled a list of accredited medical schools that offer plastic surgery training for residency. Data were collected on demographics, academic rank, and research output using the Doximity, LinkedIn, and Scopus databases. Data analyses were performed with a Mann-Whitney U test and a Kruskal-Wallis test. Results: Women who were black, indigenous, and/or other color occupied only 6.25% of plastic surgery faculty leadership positions in North America. There are more women and underrepresented minorities in leadership positions in Canada, when compared with the USA, relative to each country's demographic. In both countries, women and underrepresented minority plastic surgeons had fewer publications, citations, and years of active research. Interestingly, having women in leadership positions was associated with a higher number of women faculty members. Conclusions: Gender and racial disparity exist in academic plastic surgery in North America. Several changes are required in order for women and underrepresented minorities in medicine to have an equal chance at career advancement. Better representation and diverse leadership have the potential to bring about equity, diversity, and inclusion in academic plastic surgery.